2012
DOI: 10.1001/archoto.2012.1081
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targeting of Ultrasonographic Contrast Agent for Detection of Head and Neck Squamous Cell Carcinoma

Abstract: Objective To investigate the feasibility of ultrasonographic (US) imaging of head and neck cancer with targeted contrast agents both in vitro and in vivo. We hypothesize that conjugation of microbubble contrast agent to tumor-specific antibodies may improve US detection of head and neck squamous cell carcinoma (HNSCC). Design Preclinical blinded assessment of anti-EGFR and anti-CD147 microbubble contrast agents for US imaging of HNSCC. Setting Animal study. Subjects Immunodeficient mice. Intervention I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…In a preclinical setting Targestar-B was targeted to epidermal growth factor receptor (EGFR) and CD147 expressed in head and neck squamous cell carcinoma, where using the dual targeting was reported as most promising [47]. Although Eselectin is not a novel target, its up-regulation due to inflammation can also be used to monitor tumour progression and metastasis.…”
Section: Novel Targeting Strategiesmentioning
confidence: 99%
“…In a preclinical setting Targestar-B was targeted to epidermal growth factor receptor (EGFR) and CD147 expressed in head and neck squamous cell carcinoma, where using the dual targeting was reported as most promising [47]. Although Eselectin is not a novel target, its up-regulation due to inflammation can also be used to monitor tumour progression and metastasis.…”
Section: Novel Targeting Strategiesmentioning
confidence: 99%
“…Results from this study revealed a 2.1- and 1.5-fold increase in the mean molecular US signal when using dual-targeted MBs versus the VEGFR2 and α V β 3 integrin-targeted MBs, respectively. Similar molecular US image enhancement patterns were observed when using a dual-targeted MB to both EGF receptor and extracellular matrix metalloproteinase inducer (CD147) compared with the single-targeted MB strategies [104]. As shown by Warram et al , multitargeted MBs produce a synergistic effect when used for molecular US imaging of tumor angiogenesis [91].…”
Section: Preclinical Molecular Us Imaging Of Tumor Angiogenesismentioning
confidence: 67%
“…Future work should continue the development and validation of clinically translatable highresolution DCE-US imaging methods for more accurately quantifying tumor angiogenic biomarkers throughout an entire tumor mass. Actively targeting the MB contrast agents to tumor neovascularity and over-expressed biomarkers may also help improve angiogenic biomarker quantification given enhanced visualization of the tumor neovascular network [19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%